Examining the impact of slide burnishing parameters on the 3D surface features of medium carbon steel - Tesfom Kebede, Frezgi; Felho, Csaba (Journal of Production Engineering, 2024)
Burnishing is a non-cutting finishing technique in which pressure is applied to plastically deform the irregularly distributed surface materials. In this process, the peaks of the surface are pressed into the valleys with a hard tool, resulting in a smoother surface with improved properties. The influence of brunishing parameters such as brunishing force, feed rate and number of passes on the 3D surface roughness of medium carbon steel was analyzed. An orthogonal L9 array Taguchi design was used to create a robust experiment. A CNC milling machine and a confocal microscope were used to grind and measure the workpiece surface. The topography roughness responses Sq, Sv, Sz and Sa were used to evaluate the roughness changes. The optimal parameters for brunishing were a feed rate of 0.05 m/min, 2 passes and a force of 80N for Sq and Sa and a force of 100N for Sv and Sz. This research is expected to provide insights into optimizing mass finishing processes to improve surface integrity, contributing to advances in manufacturing and materials science.